The junction of the human dignity and rights issue ontology and ethics of human dignity - Turco, Giovanni (Derecho Público Iberoamericano, 2020)
The human dignity has been deformed by post-kantian modern thought. It has raised many legal and ethical paradoxes. The problem is resolved satisfactorily by resorting to the notion of dignity of classical and Christian philosophy.